1991
DOI: 10.1159/000204888
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction following Splenectomy in Idiopathic Myelofibrosis: A Study of 10 Patients

Abstract: The hepatic abnormalities that developed after the splenectomy in 10 subjects with idiopathic myelofibrosis were analyzed. In all patients in whom a liver biopsy was performed during the splenectomy, ex-tramedullary hematopoiesis was demonstrated, consisting of dysmorphic megakaryocytes primarily localized in the sinusoids, often accompanied by erythroid precursors. Following splenectomy, a significant increase in both the liver size and serum levels of alkaline phosphatase, bilirubin or γ-glutamyl transpeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…We paid particular attention to the behavior of the bone marrow and spleen, given the renewed interest in the latter in oncology (13,14). We interrogated the stability of hepatic uptake, critical for qualitative imaging, because the liver has a potential hematopoietic role that may translate as variation of uptake during chemotherapy (15). We further investigated the interrelation between 18 F-FLT and 18 F-FDG in these organs and the potential for 18 F-FLT uptake to anticipate the classic toxicity endpoint of peripheral blood counts and blood smears.…”
mentioning
confidence: 99%
“…We paid particular attention to the behavior of the bone marrow and spleen, given the renewed interest in the latter in oncology (13,14). We interrogated the stability of hepatic uptake, critical for qualitative imaging, because the liver has a potential hematopoietic role that may translate as variation of uptake during chemotherapy (15). We further investigated the interrelation between 18 F-FLT and 18 F-FDG in these organs and the potential for 18 F-FLT uptake to anticipate the classic toxicity endpoint of peripheral blood counts and blood smears.…”
mentioning
confidence: 99%
“…Moreover, there are some unique postoperative complications such as massive hepatomegaly due to extramedullary hematopoiesis in 16%-24% of splenectomized MMM patients leading to liver failure in some cases, post-splenectomy extreme thrombocytosis in up to 50% of splenectomized MMM patients, and the major concern of leukemic transformation. All these factors, together with the knowledge that splenectomy has not been shown to improve overall survival in MMM patients, must be strongly considered before proceeding for splenectomy to manage PH [3,[32][33][34] . PH caused by intra-hepatic or portal obstruction requires interventional or surgical portosystemic shunting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, massive hepatomegaly due to compensatory myeloid metaplasia of the liver develops in 16–24% of patients, some of which die from liver failure. 39 Post-splenectomy thrombocytosis that increases the risk of thrombosis, especially in the splenoportal vein tract, 40 is observed in 20% of patients. Following splenectomy, a higher rate of blast transformation has also been registered in one study, 41 although this was not confirmed by others.…”
Section: Splenectomymentioning
confidence: 99%